Pengembangan Kurikulum Berbasis Pendidikan Spiritualitas dalam Kearifan Lokal di Jawa - Majid, Abdul; Haryanto, Sri; Shidiq, Ngarifin; Khoiri, Ahmad; Sunarsi, Denok (JTP - Jurnal Teknologi Pendidikan, 2018)
The research objective is to examine the development of a curriculum based on spirituality education in Indonesian local wisdom, descriptive qualitative methods with literature review, and analysis techniques using the triangulation of miles and huberman. Result shows the development of a curriculum based on spiritual education in local wisdom is only a fraction of the values ​​and content of various knowledge about local wisdom of the Indonesian nation in general and the Javanese society in particular. Even then, we still need to discuss scientifically and thoroughly related to local wisdom. And it will be more interesting, if it is examined from a specific scientific perspective, for example looking at local wisdom from the side of law, da’wah or communication, anthropology and sociology, mass psychology, even national economy and politics. Therefore, local wisdom as the culture of the local community is a big investment for the development of Islam in Indonesia. An investment that must be nurtured and sown in our education, so that the presence of Islam in the midst of the old and new culture is always shady and calm in Indonesian soil.